The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1094/ats-2007-1218-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Does Spray Coverage Influence Fungicide Efficacy Against Dollar Spot?

Abstract: Chlorothalonil and myclobutanil were applied separately to creeping bentgrass using two sets of nozzles: two low‐drift nozzles that provided incomplete coverage [Teejet Turbo Turfjet nozzle (1/4TTJ04‐VS) and the Raindrop RA‐4 nozzle (35654‐2)], and two nozzles that provided nearly complete coverage [XR Teejet flat fan nozzle (XR11004‐VS) and the Teejet Air Induction nozzle (AI1004‐VS)], as assessed using water‐sensitive paper. Spray volume and pressure were equivalent with all nozzles. For both fungicides test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In addition to the assay and analytical method, inconsistent fungicide deposition and sampling techniques may have also contributed to the observed variability. Vincelli & Dixon () demonstrated that fungicide coverage on a two‐dimensional paper surface was ‘near complete’ using air‐induction nozzles similar to those used in the present study. However, fungicide coverage within a three‐dimensional turfgrass plant and over an experimental area may be significantly less than complete and may have contributed to the observed variability.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to the assay and analytical method, inconsistent fungicide deposition and sampling techniques may have also contributed to the observed variability. Vincelli & Dixon () demonstrated that fungicide coverage on a two‐dimensional paper surface was ‘near complete’ using air‐induction nozzles similar to those used in the present study. However, fungicide coverage within a three‐dimensional turfgrass plant and over an experimental area may be significantly less than complete and may have contributed to the observed variability.…”
Section: Discussionmentioning
confidence: 64%
“…1). Vincelli and Dixon (17) demonstrated a similar overall pattern for TurfJet and XR nozzles at 1.5 gal/1000 ft². In the present study, the Air Induction and Turbo Drop Twin Fan created a blend of larger and smaller droplets.…”
Section: Influence Of Nozzle Type and Water Volumementioning
confidence: 74%
“…While these studies provide insight into dollar spot control, there is a lack of information on the effect of spray volume in combination with different nozzle types. Spray technology for turfgrass applications, however, has received some recent attention in research (3,4,5,6,8,17) and trade (13,18) publications. However, there is still a need for more information.…”
Section: Introductionmentioning
confidence: 99%
“…Other than chlorothalonil providing improved dollar spot control in Crenshaw using the low spray volume in 2008, chlorothalonil results do not fully support the findings of McDonald et al (9). Improving spray coverage can enhance dollar spot control with fungicides (11). McDonald et al (9) applied the fungicides at right angles, which likely improved coverage versus a one direction application.…”
Section: Summary and Recommendationsmentioning
confidence: 99%